Improving Science Learning Outcomes of Grade V Students of SDN Telang 2 Through Project Based Learning - Hendra Herlambang Nugroho; Galah Tri Anggada; Sahrul Nizam; Agung Setyawan; Hao Yu (Journal of Action Research in Education, 2025)
This research aims to determine the results of science learning, especially regarding the growth of green beans and group learning activities of class V students at SD Negeri Telang 2 through the application of the Project Based Learning learning model. The conclusion of the research is that the percentage of completeness obtained through completing project assignments in groups using the project based learning model before the intervention was 21%. In cycle I it increased to 67%, and in cycle II the increase reached 70%. It can be concluded that the use of the Project Based Learning learning model is effective in increasing science learning outcomes, especially in the growth of green beans, reaching up to 70%.